Discovery of a sexual cycle in Talaromyces amestolkiae. (1st January 2016) - Yilmaz, Neriman; Hagen, Ferry; Meis, Jacques F.; Houbraken, Jos; Samson, Robert A.
Abstract : Talaromyces amestolkiae is a common cosmopolitan species that has been cultured from indoor house dust, sputum and lungs from cystic fibrosis patients, indoor air, wheat, soil, pineapple, sculptures and manure. It was described as an asexual Talaromyces species and was reported to produce black sclerotia. In this study we report on the induction of sexual reproductive structures in T. amestolkiae . The mating type of 18 T. amestolkiae strains was determined with MAT -specific primers. Subsequently opposite mating types were inoculated on oatmeal agar and malt-extract agar and incubated 6–20 wk at 25 and 30 C in darkness. After incubation single ascospore isolations were made and evidence of recombination in the offspring was examined by amplified fragment length polymorphism and pairwise homoplasy index test, which is implemented in Splitstree4. The offspring displayed clear evidence of recombination on a genetic level as shown in the variations observed between banding patterns in the amplified fragment length polymorphism. Also a net-like and reticulated NeighborNet was observed and the pairwise homoplasy index test for recombination supported the presence of recombination ( P = 0.003372). The distribution of MAT1-1 and MAT1-2 genes in the progeny showed a close to 1 : 1 ratio. Talaromyces amestolkiae is only the second heterothallic Talaromyces species to produce ascomata and ascospores under laboratory conditions.